Cheerleading as a part of Finnish sports culture : an overview of the development of cheerleading in post-modern Finnish sports culture from 1979 to 2018 - Nykänen, Riikka (2018)
Cheerleading was born in the United States of America in the late 19th century and arrived in Finland in 1979. First, cheerleading was a sideline activity of other sports, but later it became a sport of its own. Now, cheerleading has become a visible part of Finnish sports culture and a popular alternative next to traditional sports. There has not been done academic studies about the development of Finnish cheerleading before this research. The purpose of this thesis was to present the development of Finnish cheerleading from years 1979 until 2018. The main focus is on the time period from 2005 until 2015, when the development of cheerleading as sport, has been quick. Furthermore, the aim of this study was to study the development of cheerleading in post-modern Finnish sports culture. This is a historic research about Finnish cheerleading. The data was collected from resources, such as annual reports of the Finnish Cheerleading Federation, newspapers, websites, international researches and books. The qualitative methods were used, however some of the numeric data was used to support and enable the comprehensive analyzation of the data. The relation between the changes in Finnish sports culture and cheerleading, is clear. Cheerleading arrived in Finland during the age of divergent activity and characteristics typical for that age, such as the popularity of team sports, explains partly the integration of cheerleading. The data illustrate that cheerleading has integrated into post-modern Finnish sports culture. Cheerleading has developed from a spontaneous entertainment to a well-organized sport, acknowledged by the government and other associations nationally and internationally. Cheerleading has become more professional in terms of administrative matters and advanced education of coaches. The active and enthusiastic people in the field of cheerleading, international success and accessibility of cheerleading, have been factors behind the rapid growth. Furthermore, in 2016, cheerleading was 12th most popular sport among children and youth. Professionalization of the administration of FCF, strategy and constant development, have had key roles in integration of cheerleading as a part of Finnish sports culture.